2016
DOI: 10.1073/pnas.1607032113
|View full text |Cite
|
Sign up to set email alerts
|

Spatial heterogeneity of climate change as an experiential basis for skepticism

Abstract: We postulate that skepticism about climate change is partially caused by the spatial heterogeneity of climate change, which exposes experiential learners to climate heuristics that differ from the global average. This hypothesis is tested by formalizing an index that measures local changes in climate using station data and comparing this index with survey-based model estimates of county-level opinion about whether global warming is happening. Results indicate that more stations exhibit cooling and warming than… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
49
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(51 citation statements)
references
References 37 publications
2
49
0
Order By: Relevance
“…For example three studies find that 10 year summer temperature trends are positively related to beliefs about human-caused global warming in the US [19,64,66]. In addition, an index representing the ratio of previous record high temperatures to record low temperatures over several years (with more record high temperatures expected under a warming climate) is associated with estimates of county-level climate opinions in the US [12,69]. However, other studies that have focused on longer-term temperatures or trends have found little to no effect on climate opinions [28,30,32,34,70,71].…”
Section: The Effect Of Objective Temperature Experiences On Climate Omentioning
confidence: 99%
See 2 more Smart Citations
“…For example three studies find that 10 year summer temperature trends are positively related to beliefs about human-caused global warming in the US [19,64,66]. In addition, an index representing the ratio of previous record high temperatures to record low temperatures over several years (with more record high temperatures expected under a warming climate) is associated with estimates of county-level climate opinions in the US [12,69]. However, other studies that have focused on longer-term temperatures or trends have found little to no effect on climate opinions [28,30,32,34,70,71].…”
Section: The Effect Of Objective Temperature Experiences On Climate Omentioning
confidence: 99%
“…[31,32,38,66]), whereas in other cases respondents are aggregated by zip code, county, or even state levels (e.g. [8,12]). The varying degrees of mismatch between respondent locations and weather or climate 'treatments' introduces uncertainties into any assessment of treatment effects.…”
Section: Variation In Geographic Coveragementioning
confidence: 99%
See 1 more Smart Citation
“…It seems unlikely that climate models will be able to provide the local-scale, specific, reliable, and trusted information required for most private adaptation decisions. Instead, direct experience of weather events is likely to be an important information source, with several studies suggesting a link between experience of weather anomalies and stated belief in climate change (Howe et al, 2014;McCright et al, 2014;Kaufmann et al, 2017). Therefore, how well people learn from experience in nonstationary, stochastic environments has important implications for the rate of adaptation and the economic costs associated with climate change.…”
Section: Introductionmentioning
confidence: 99%
“…Impressions on the past local climate affect individual beliefs and behaviors, e.g. people living in areas turning cold are more likely to doubt whether the earth is warming [24,25], and individuals are capable of adjusting their expectation of and response to the future climate by learning from the past [26]. Therefore, the past climate may also affect the hotel business: unpleasant weather in the past may lead to a loss of visitors and lower room rates, and thus a reduction of revenue and profit.…”
Section: Resultsmentioning
confidence: 99%